Recent Deformation in the Bottom Sediments of Western and Southeastern Lake Ontario and its Association with Major Structures and Seismicity - Thomas, R.; Wallach, J.; McMillan, R.; Bowlby, J.; Frape, S.; Keyes, D.; Mohajer, A. (Géographie physique et Quaternaire, 1993)
ABSTRACTGeophysical surveys, undertaken in the Toronto-Burlington corridor of western Lake Ontario and in the Rochester Basin of southeastern Lake Ontario, revealed the presence of features affecting the young lake-bottom sediments. In the western part of the lake, they include inferred pop-ups in bedrock, and plumose structures, dark linear patterns, and linear belts of circular to elliptical signatures in the modern mud. In southeastern Lake Ontario the glacial and post-glacial sediments display vertical separations of on the order of 10-15 m. Pop-ups are tectonically-induced structures. The features in the modern mud commonly parallel the orientation of P-stresses measured in Paleozoic rocks nearby and, along with the pop-ups, are spatially related to an aeromagnetic lineament. Furthermore, all of these features occur within a seismically active belt. The vertical displacements of the layered glacial and post-glacial sediments, within the Rochester Basin, are located along the southern margin of the postulated WSW extension of the seismically active St. Lawrence rift system and are interpreted to be due to faulting. The geologically young age of the sediments affected by the various deformational features, along with the characteristics of the features themselves, suggest that the lake-bottom sediments surveyed in this study may have recorded the effects of neotectonic processes.